2006
DOI: 10.1902/jop.2006.77.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Vascular Endothelial Growth Factor in Cyclosporin A‐Induced Gingival Overgrowth in Rats

Abstract: The results of this study suggest that increased VEGF expression may be associated with the pathogenesis of CsA-induced gingival overgrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 41 publications
(57 reference statements)
1
30
0
Order By: Relevance
“…Some studies have linked the adverse effects of osteoporosis and osteopenia to use of CsA. 4,5,21,30,31 These features regarding alveolar bone metabolism would be associated with increased osteoclastic activity and reduction of bone formation in the presence of CsA. In this study, the authors suggested that CsA immunosupression might have caused a decrease in periodontal breakdown.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Some studies have linked the adverse effects of osteoporosis and osteopenia to use of CsA. 4,5,21,30,31 These features regarding alveolar bone metabolism would be associated with increased osteoclastic activity and reduction of bone formation in the presence of CsA. In this study, the authors suggested that CsA immunosupression might have caused a decrease in periodontal breakdown.…”
Section: Discussionmentioning
confidence: 78%
“…20 Epithelial tissue also showed increased thickness based on an increase of basal stem cell proliferation stimulated by CsA and inflammatory conditions. 21 A study to investigate the effect of periodontal treatment in renal transplant recipients cited that the study results could support the hypothesis that plaque is a significant contributing factor in the development of cyclosporine-induced overgrowth. 22 Additionally, the results show that in patients without periodontal therapy, complications of cyclosporine had adverse effects on oral and periodontal health due to development of clinical overgrowth, in contrast to patients who had periodontal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This model is characterized by accumulation of dental plaque and increased infiltration of inflammatory cells that lead to a degradation of periodontal connective tissue and alveolar bone (Keles et al, 2005). In recent years, the effects of CsA therapy on soft tissues of the periodontium have been extensively investigated in vitro (Bartold 1989;Schincaglia et al, 1992) and in vivo (Seymour et al, 1987;Somacarrera et al, 1994;Cetinkaya et al, 2006aCetinkaya et al, , 2006b. It has been reported that 10 mg/kg daily doses of the drug 720 CETINKAYA ET AL TOXICOLOGIC PATHOLOGY provide plasma peak and trough levels of 1000 and 750 ng/ml (Wassef et al, 1985) and blood levels of CsA between 100-400 ng/ml are sufficient to promote immunosupression in animals (rats, dogs, and monkeys) as well as in humans (Fischer and Klinge, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Gingival tissues, removed from the alveolar bone, were placed immediately in a sterile saline solution and frozen at −80°C until biochemical analysis [37]. In brief, before grinding, tissue was blotted, weighed on a microbalance, and placed into a sufficient volume of phosphate buffered saline (PBS; 4°C; pH: 7.0) containing a protease inhibitor (5  μ g/mL aprotinin, 1 mM EDTA) to a dilution of 10 mg tissue/mL PBS plus protease inhibitor solution.…”
Section: Methodsmentioning
confidence: 99%